Immunogenicity and protectivity of Plasmodium falciparum EBA-175 peptide and its analog is associated with alpha-helical region shortening and displacement (2003)
EBA-175 protein is used as a ligand in the binding of P. falciparum to red blood cells (RBCs). Evidence shows that the conserved peptide 1779 from this protein (with high red blood cell binding ability and known critical erythrocyte binding residues) plays an important role in the invasion process. This peptide is neither immunogenic nor protective; analogs having critical residues replaced by amino acids with similar volume or mass but different polarity were synthesized and inoculated into Aotus monkeys, and elicited different immunogenic and protective responses. Nuclear Magnetic Resonance (1H-NMR) studies revealed that peptide analog 21696 (non-immunogenic and non-protective) presents a large helical fragment, that the peptide 14012 (immunogenic and non-protective) helical fragment is smaller, while the peptide 22812 (immunogenic and protective) [alpha]-helix is shorter in a different region and possesses greater flexibility at its N-terminus. The presence of methionine residues could affect the structural stability of peptide 22812 and ultimately its immunological response. Our results suggest a new strategy for designing a new malaria multi-component subunit-based vaccine.